Thoracoabdominal Aortic Aneurysm in a HIV-positive Patient - Lucas,Márcio Luís (2017)
Abstract Advent of antiretroviral therapy has increased survival of patients with human immunodeficiency virus (HIV) infections, with the result that some of these patients now develop degenerative diseases, such as atherosclerotic aneurysms. Degenerative thoracoabdominal aortic aneurysm is rare in HIV patients. In this report, a 63-year-old male patient with HIV submitted to open repair of thoracoabdominal aortic aneurysm. The patient did not suffer any type of complication in the perioperative period and remained well in a 28-month follow-up period. In summary, open repair still remains a good alternative for aortic complex aneurysms even in HIV patients.